Peningkatan Kinerja Guru Pada Masa Pandemi Covid-19 Dalam Melaksanakan Pembelajaran Melalui Supervisi Klinis Kepala Sekolah - Nuraini Nuraini (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
Teaching eligibility in pandemic times is not enough to be measured only based on formal education but must also be measured based on how the teacher's ability to teach and master material sessions, master, choose and use methods, media and learning evaluations. In this regard, that the ability of teachers in need to be our concern together develops complete learning during the covid-19 pandemic. The purpose of this school action research is to find out the extent of principal coaching through academic supervision to improve teacher performance in carrying out learning. In school action research is carried out in 3 cycles, from the results of actions taken proven to improve the ability of teachers by achieving ideal standards. From 63.14% in cycle I, it can increase to 70.71% in cycle II, and cycle III increases to 76.43%. The results of this action study showed that coaching through the clinical supervision of the principal can improve the performance of teachers in carrying out learning with completion reaching 100%